5-Bromo-1H-indole-3-carbaldehyde 2-nitrophenyl-hydrazone hemihydrate - Ali, Hapipah Mohd; Ng, S.W.; Halim, A.; Nadiah, S. (International Union of Crystallography, 2005)
In the title compound, C16H11BrN4O 3·0.5H2O, the water molecule lies on a twofold rotation axis. Symmetry-related molecules are linked to form an N-H⋯O and O-H⋯O hydrogen-bonded layer structure. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.